Perindopril decreases angiotensin-converting enzyme 2 (ACE2) expression in human adipocytes exposed to SARS-CoV-2 S1 spike protein - Harsoyo, Primasitha M.; Ardiana, Meity; Hermawan, Hanestya O.; Purnamasari, Yeni; Anandita, Faizal A. (Narra Sains Indonesia, 2024)
The expression of angiotensin-converting enzyme 2 (ACE2) in the adipose tissues of obese patients needs further study, as it may aid infection and serve as a viral reservoir. There has been controversy over whether to use ACE inhibitors to prevent coronavirus disease 2019 (COVID-19) severity. Perindopril, an ACE2 inhibitor, has been proposed; however, its relationship with COVID-19 has not yet been clear. The aim of this study was to investigate the effect of perindopril to reduce the expression of ACE2 and pro-inflammatory cytokine in adipocytes exposed to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Enzymatic isolation of adipose tissues was performed from obese male donor patients aged 30–50 years, then exposed it with SARS-CoV-2 S1 spike protein. This study also included human recombinant ACE2 (hrsACE2) as a comparison to perindopril. The expression of ACE2 was evaluated using ELISA. Our data indicated that SARS-CoV-2 Spike protein exposure increased ACE2 expression significantly. Administration of perindopril decreased ACE2 expression (43.37 µg/mL) significantly compared to the positive group (80.31 µg/mL) (p<0.001). Perindopril administration also decreased IL-6 levels significantly compared to positive group(p<0.001). This study highlights that perindopril could reduce the ACE2 expression and pro-inflammatory cytokine levels in adipocytes exposed to SARS-CoV-2 S1 spike protein.